Putting the Squeeze on Airway Epithelia - Park, Jin-Ah (Physiology (Bethesda), 2015)
Asthma is characterized by chronic inflammation, airway hyperresponsiveness, and progressive airway remodeling. The airway epithelium is known to play a critical role in the initiation and perpetuation of these processes. Here, we review how excessive epithelial stress generated by bronchoconstriction is sufficient to induce airway remodeling, even in the absence of inflammatory cells.